2010
DOI: 10.1186/1472-6807-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Structural motif screening reveals a novel, conserved carbohydrate-binding surface in the pathogenesis-related protein PR-5d

Abstract: BackgroundAromatic amino acids play a critical role in protein-glycan interactions. Clusters of surface aromatic residues and their features may therefore be useful in distinguishing glycan-binding sites as well as predicting novel glycan-binding proteins. In this work, a structural bioinformatics approach was used to screen the Protein Data Bank (PDB) for coplanar aromatic motifs similar to those found in known glycan-binding proteins.ResultsThe proteins identified in the screen were significantly associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…We conducted a systematic search of the TLP models to locate regions that might interact with (1, 3) β-D glucan (13). The search suggested that the glucan could be docked at the primary polysaccharide-binding site (CQTGDCGG) located in the cleft (26). In our study, this motif was observed exclusively in TLP1, -2, and -8 (Table S2).…”
Section: Discussionmentioning
confidence: 67%
“…We conducted a systematic search of the TLP models to locate regions that might interact with (1, 3) β-D glucan (13). The search suggested that the glucan could be docked at the primary polysaccharide-binding site (CQTGDCGG) located in the cleft (26). In our study, this motif was observed exclusively in TLP1, -2, and -8 (Table S2).…”
Section: Discussionmentioning
confidence: 67%
“…(26, 27) Two or three coplanar, closely-spaced, surface-accessible aromatic amino acids are frequently involved in glycan binding. (28) In the present study, we investigate the role of clustered, surface-accessible aromatic amino acids within epsilon toxin in mediating binding of the toxin to cells and to its putative receptor, HAVCR1.…”
Section: Resultsmentioning
confidence: 99%
“…9A). Trp is typically rare on the protein surface, with the exception of carbohydrate-binding sites where it is an overrepresented residue and can play a crucial role in C-H/π-stacking with the B-face of the pyranose ring [38][40].…”
Section: Resultsmentioning
confidence: 99%